Workers' Compensation Elements in Different Jurisdictions in the United States. Issue 12 (December 2020) - Taylor, Tanisha K.; Mueller, Kathryn L.; Blink, Robert C.; McKinney, David W.; Silverman, Warren; Das, Rupali
Abstract : N/A: Over the decades, the workers' compensation system has provided many injured workers with a significant guarantee of both medical and financial support when they have been injured on the job. To be effective, workers' compensation systems at a minimum should include principles that require the addressing of medical causation, determination of an individual's functional ability both pre- and post-injury to include activity restrictions, return-to-work capability and disability, meeting jurisdiction-specific reporting requirements of the workers' compensation reporting requirements, and having knowledge of other perspectives of the various authorities and jurisdictions present in the United States. ACOEM lays out a description of various aspects of workers' compensations systems in the United States, with recommendations for minimal standards and best practices. This paper limits itself to the discussion of jurisdictions within the United States and ACOEM strongly recommends that providers consult directly with the states in which they are working as there are state variations in workers' compensation.